The deportation machine : America's long history of expelling immigrants - Goodman, Adam (Historian) (Politics and society in modern America., 2020)
Constant headlines about deportations, detention camps, and border walls drive urgent debates about immigration and what it means to be an American in the twenty-first century. The Deportation Machine traces the long and troubling history of the US government's systematic efforts to terrorize and expel immigrants over the past 140 years. This provocative, eye-opening book provides needed historical perspective on one of the most pressing social and political issues of our time. In a sweeping and engaging narrative, Adam Goodman examines how federal, state, and local officials have targeted various groups for expulsion, from Chinese and Europeans at the turn of the twentieth century to Central Americans and Muslims today. He reveals how authorities have singled out Mexicans, nine out of ten of all deportees, and removed most of them not by orders of immigration judges but through coercive administrative procedures and calculated fear campaigns. Goodman uncovers the machine's three primary mechanisms--formal deportations, "voluntary" departures, and self-deportations--and examines how public officials have used them to purge immigrants from the country and exert control over those who remain. Exposing the pervasive roots of anti-immigrant sentiment in the United States, The Deportation Machine introduces the politicians, bureaucrats, businesspeople, and ordinary citizens who have pushed for and profited from expulsion. This revelatory book chronicles the devastating human costs of deportation and the innovative strategies people have adopted to fight against the machine and redefine belonging in ways that transcend citizenship.